Magnitude and Associated Factors of Herbal Medicine Use During Pregnancy Among Women Attending Antenatal Care in Public Health Institutions of Central Tigray, Northern Ethiopia (2020): Facility-Based Cross-Sectional Study - Hailemikael Gebrekidan; Gebregziabher Kidanemariam (Journal of Pregnancy)
Conclusion and Recommendation: Based on our results, herbal medicine use during pregnancy is highly practiced in this study, and occupation, residency, educational status, and average monthly income were the significantly associated factors of herbal medicine use during pregnancy. There is a need to educate and counsel pregnant women on the harmful effects of herbal medicine use during pregnancy by the health care personnel and health extension worker.